A general technique to embed non-uniform discontinuities into standard solid finite elements - Manzoli, O. L. [UNESP]; Shing, P. B. (Elsevier, 2006)
A general technique to embed non-uniform displacement discontinuities into standard solid finite elements is presented. The technique is based on the decomposition of the kinematic fields into a component related to the deformation of the solid portion of the element and one related to the rigid-body motion due to a displacement discontinuity. This decomposition simplifies the incorporation of discontinuity interfaces and provides a suitable framework to account for non-uniform discontinuity modes. The present publication addresses two families of finite element formulations: displacement-based and stress hybrid finite element. © 2005 Elsevier Ltd. All rights reserved.
Keywords: Embedded discontinuity; Finite elements; Non-uniform discontinuity modes; Stress hybrid element; Stress locking; Strong discontinuity; Decomposition; Deformation; Finite element method; Interfaces (materials); Kinematics; Stresses; Embedded systems